Grapefruit Juice Flavanones Modulate the Expression of Genes Regulating Inflammation, Cell Interactions and Vascular Function in Peripheral Blood Mononuclear Cells of Postmenopausal Women - Krga, Irena; Corral-Jara, Karla Fabiola; Barber-Chamoux, Nicolas; Dubray, Claude; Morand, Christine; Milenkovic, Dragan (Frontiers in Nutrition, 2022)
Grapefruit is a rich source of flavanones, phytochemicals suggested excreting vasculo-protecting effects. We previously showed that grapefruit juice (GFJ) flavanones reduced postmenopausal women's pulse-wave velocity (PWV), a measure of arterial stiffness. However, mechanisms of flavanone action in humans are largely unknown. This study aimed to decipher molecular mechanisms of flavanones by multi-omics analysis in PBMCs of volunteers consuming GFJ and flavanone-free control drink for six months. Modulated genes and miRNAs were identified using microarrays. Bioinformatics analyses assessed their functions, interactions and correlations with previously observed changes in PWV. GFJ modified gene and miRNA expressions. Integrated analysis of modulated genes and miRNA-target genes suggests regulation of inflammation, immune response, cell interaction and mobility. Bioinformatics identified putative mediators of the observed nutrigenomic effect (STAT3, NF-B) and molecular docking demonstrated potential binding of flavanone metabolites to transcription factors and cell-signaling proteins. We also observed 34 significant correlations between changes in gene expression and PWV. Moreover, global gene expression was negatively correlated with gene expression profiles in arterial stiffness and hypertension. This study revealed molecular mechanisms underlying vasculo-protective effects of flavanones, including interactions with transcription factors and gene and miRNA expression changes that inversely correlate with gene expression profiles associated with cardiovascular risk factors. Clinical Trial Registration: This work is a part of the study registered at ClinicalTrials.gov www.clinicaltrials.gov/ct2/show/NCT01272167, identifier: NCT01272167.